People participating in the 1986 y-Walk - Brock, Trish (photographer):::Creator::::::::::::
Negative shows a group of men and women participating in the 1986 y-Walk. They are walking in the street where sidewalk would normally be. There is a chain linked fence, but there are no buildings on that side of the street. Some of participants are carrying balloons and wearing tee shirts that read: "Walk for women. YWCA 1986."